The The Role of Teachers in the Character Building of Students at Karitas Watuneso High School - Lisman Wati; Nurdin H Rahman S; Murjoli Rodja (Program Studi Pendidikan Ekonomi, IKIP Budi Utomo Malang, 2020)
The role of the teacher in shaping the character of students is one important component in shaping the character of students to become better. Based on the results of research carried out at Karitas Watuneso high school that in shaping the character of students the teacher provides motivation, advice, guidance, and becomes an example for students who should be encouraged and replicated by the students participants. The type of motivation that teachers do at Karitas Watuneso high school is by providing scholarships for students, the type of guidance provided by teachers at Karitas Watuneso high school is implemented during the learning process and when other spiritual or extra-curricular activities are carried out, the role of the teacher in shape the character of students by giving advice to students, namely face to face with students specifically in one particular room, in addition to forming the character of participants in high school Karitas Watuneso teacher is an example thas is used as an example by students relating to attitudes, appearance, time discipline, as well as courtesy in speaking and mutual respect both teacher-teacher and teacher with students. The application of character that has been carried out at Karitas Watuneso senior high school is to provide stimulus for students before learning begins consisting of praying before starting learning and after learning, tidying the tables and chairs before learning begins, reminding students of the material being taught, and providing motivation for students related to the material to be taught. The purpose of providing motivation, guidance, advice, and being an example for students is that students know every wrong action that has been done by students and students are motivated to think creatively, learn independently, honestly, be responsible, discipline time, and neatly married school and have good manners.